ASUHAN KEPERAWATAN PADA IBU HAMIL NY. L G2P1A0 (10 MINGGU) DENGAN EMESIS GRAVIDARUM DI CAGAR ALAM KOTA DEPOK - Usnul Divana Suleman (2022)
Background: Nausea and vomiting are normal and are often encountered during pregnancy, especially when pregnancy is in the first trimester, nausea is felt in the morning, but some can happen anytime even at night. Nausea and vomiting during pregnancy have an undeniable impact on family daily life, normal daily life, social functioning, and the development of stress, which results in physical exhaustion, malnutrition, dehydration and weakness during pregnancy. electrolyte imbalance that causes other symptoms such as nausea and weight loss. Disseminating about family health is a strategy that must be done in improving the quality of babies in the womb and can help reduce maternal and infant morbidity and mortality. In this situation, it is known if the risk factors that can be seen can harm the mother and child that can be found before pregnancy. Examples are mothers who suffer from anemia, suffer from a lack of folic acid, or habits that can affect the health of the mother and fetus. Prenatal counseling is an important element of antenatal care. Through this, those who provide services can provide education and provide recommendations on strategies to improve maternal and fetal health. The purpose of this study is to present nursing care for pregnant women, Mrs. L (G2P1A0) with nausea and vomiting accompanied by a lack of knowledge about pregnancy in the Depok City Nature Reserve. Research Methods: The research uses descriptive quantitative and qualitative methods, and conducts interviews, observations, and documentation on clients directly with a sample of 1 respondent. Research Results: The results of the study showed that most pregnant women with nausea and vomiting have signs and symptoms, one of which is easily tired when doing physical activities, unhealthy sleep patterns, and no appetite. Conclusion: It is hoped that nurses as medical personnel can explain better about health education for pregnant women with nausea and vomiting in order to increase knowledge of pregnant women about the risk of nausea and vomiting during the process of pregnancy problems. Keywords: Pregnancy, nausea and vomiting, first trimester